Sleep Deprivation and Unwanted Behaviours in a Four Year Old Warmblood Mare with Upper Oesophageal Sphincter Aplasia. - Ahern , Tom (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Reports of unwanted behaviours in horses as a primary presentation, ranging in severity from distracting to extremely dangerous were becoming more common. This case presented with the owner rider considering retirement for the horse if its unwanted behaviours, which were at times extremely dangerous, could not be resolved. A history of an inability or reluctance to attain recumbent sleep, with resultant sleep deprivation led to further investigations. Upper oesophageal aplasia was one of the findings. Surgery to stabilise the palato-pharynx was recommended based on previous experiences with cases of sleep deprivation with accompanying upper oesophageal sphincter aplasia. Post operatively the horse was able to achieve recumbent sleep. Improvements in behaviour followed which facilitated the horses return to successful competition. A potential association between sleep deprivation, upper oesophageal aplasia, oesophageal reflux and palato-pharyngeal instability was discussed.